Effect of acute caffeine consumption on the maximum force and blood lactate levels in sedentary young: Randomized clinical trial - Arteaga-Sacro, Amy Andrea; Villota-Bedoya, Diego Fernando (Universidad y Salud, 2016)
Objective: Demonstrate the effect of caffeine in acute consumption on maximum strength and lactate levels. Materials and methods: Single-blind parallel group randomized controlled clinical trial. 92 subjects were selected, 43 randomly assigned to the caffeine intake group (1.3 mg/Kg) or placebo control. The 1RM test was used to measure maximum strength and lactate by spectrophotometry before and after 1 hour of ingestion of caffeine (1.3 mg/Kg) or placebo. Statistical analysis with t-student, percentage change and effect size with d-Cohens, p≤0.05. Results: There was a significant improvement in the maximum upper limb strength 1RM 8.3±6.0 kg with a medium effect size (26.2%; d=0.64; t=-4.36; df=41 ; p<0.01; CI: -16.9 to -6.2); and lower limb 1RM 9.2±4.9 kg with a medium effect size (25.8%; d=0.51; t=-3.16; df=41; p<0.01; CI: -17.0 to -3.7). For lactate levels, a smaller increase was observed in the experimental group 0.96±0.10 mmol/L with a small effect size (64.9%; d=0.39; t=10.8; df=41 ; p<0.01; CI:0.55 to 0.81). Conclusion: Caffeine in low doses produces a greater increase in maximum upper limb strength, maximum lower limb strength and favors a smaller increase in lactate levels.